Assessing early level of literacy: a case study on science literacy in biotechnology - H S Nugraha; Raharjo Raharjo; F Rachmadiarti (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This study aimed to know the early level of science literacy skills of 9th grade of SMPN 1 Campurdarat in biotechnology. The students who are the subjects of this study were one class consisted of thirty-five students. This study was a part of learning device development study to improve students science literacy skills. The science literacy test consisted of thirteen questions with details four questions were simple multiple choice, four question were complex multiple choice, and five questions were easy. The science literacy test consisted of all levels science literacy with details one question was level 1a, four questions were level 2, three questions were level 3, three question were level 4, one question was level 5, and one question was level 6. The assessing showed results that 11.43% students were in level 1b; 65.71% students were in level 1a; and 22.86% students were in level 2. These results were apropriate with recent PISA surveys which taken on 2015 that showed the ability of Indonesia students literacy skill were in low category